Incorporando desarrollo sustentable y gobernanza a la gestión y planificación de áreas verdes urbanas - Flores-Zolocotzi, Ramiro (Frontera Norte, 2017)
El marco teórico relacionado con áreas verdes ha incorporado conceptos de desarrollo sustentable y gobernanza, esto ha derivado en el desarrollo de indicadores económicos, ambientales y sociales aplicables en la gestión y planificación de áreas verdes. La aplicación de tales indicadores, requiere considerar: 1) concepción multidisciplinaria de desarrollo sustentable; 2) formas particulares de gestión y planificación, y 3) la participación ciudadana es importante en la gestión y planificación, aunque existen fallos que necesitan detectarse y corregirse. Se concluye que una buena gestión y planificación dependerá de fortalezas técnico–administrativas de gobiernos locales en Latinoamérica que permitan incorporar perspectivas de sustentabilidad y gobernanza. Incorporating sustainable development and governance to the management and planning of urban green areas Abstract The theoretical context related to green urban areashas incorporated concepts regarding sustainable development and governance, which has resulted in the development of economic, environmental and social indicators applicable to the the management and planning of green areas. The implementation of these indicators requires the following considerations: 1) multidisciplinary conception of sustainable development; 2) particular ways of management and planning, and 3) civic participation in management and planning, although there are shortcomings that must be detected and corrected. Good management and planning will therefore depend of the technical and administrative strengths of local governments in Latin America that will permit the incorporation of sustainable and governance perspectives.